2018
DOI: 10.1186/s12888-018-1780-1
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences among patients with substance use disorders at a referral psychiatric hospital in Kenya

Abstract: BackgroundSubstance use disorders are a major cause of health and social problems worldwide. Research evidence shows a strong graded relationship of adverse childhood experiences and substance use in adulthood. This study aimed at determining the prevalence of adverse childhood experiences and their association with substance use among patients with substance use disorders.MethodThe study used a descriptive cross-sectional design. A total of 134 patients aged 18 years and above receiving inpatient treatment fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 31 publications
3
50
0
3
Order By: Relevance
“…And from subtype of ACEs household dysfunction increasing chat by 2.093times (AOR=2.093, 95%CI=1.629-4.897). These finding was in line with other previous studies [41,42].…”
Section: Discussionsupporting
confidence: 94%
“…And from subtype of ACEs household dysfunction increasing chat by 2.093times (AOR=2.093, 95%CI=1.629-4.897). These finding was in line with other previous studies [41,42].…”
Section: Discussionsupporting
confidence: 94%
“…Was assessed using The Adverse Childhood Experiences International Questionnaire (ACE-IQ) [ 20 ]. ACE-IQ assesses adult caregivers’ experiences of childhood adversities such as child maltreatment and other traumatic stressors.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, being in the younger age group is associated with continued or resuming cannabis use during follow up (35,36). Also this may be attributed to early age of cannabis use initiation based on findings of a study in the same hospital that found 74.6% of people with substance use disorders had started use before age 20 years (5).…”
Section: Association Of Sociodemographic Characteristics and Cannabismentioning
confidence: 99%
“…National surveys reported a lifetime prevalence of 0.3% in the general population aged 15-65 years in 2017 while among secondary school students lifetime prevalence in 2016 was higher at 1.2% and 0.4% reported use in past six months (3,4). A study done among inpatients on treatment for substance use disorders, reported a higher prevalence with 8% reporting lifetime opioid use and 4.5% reporting current use (5).…”
Section: Introductionmentioning
confidence: 99%